2011
DOI: 10.3892/mmr.2011.616
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs2470152 in CYP19 is correlated to aromatase activity in Chinese polycystic ovary syndrome patients

Abstract: Abstract. CYP19 encodes aromatase, a key enzyme essential for estrogen biosynthesis. Single nucleotide polymorphism (SNP) rs2470152 in CYP19 is associated with serum estradiol (E2) level and the E2/T (estradiol/testosterone) ratio. A case-control study including 661 individuals [364 polycystic ovary syndrome (PCOS) patients and 297 controls] was conducted to assess the association of SNP rs2470152 with PCOS. The subjects were genotyped using the polymerase chain reaction-restriction fragment length polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Xu et al showed that PCOS patients had a higher frequency of (TT/TA) alleles in intron 4 of CYP19 gene, albeit they concluded it may not affect the risk of PCOS ( 20 ). Also, TC genotype of SNP rs.2470152 in CYP19 seems to inhibit aromatase activity and leads to hyperandrogenism in PCOS patients ( 21 ). Although the aforementioned researches were done on the different region (promoter) and SNPs of CYP19 gene their results are in agreement with our results based on the fact that CYP19 gene might be correlated with PCOS predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al showed that PCOS patients had a higher frequency of (TT/TA) alleles in intron 4 of CYP19 gene, albeit they concluded it may not affect the risk of PCOS ( 20 ). Also, TC genotype of SNP rs.2470152 in CYP19 seems to inhibit aromatase activity and leads to hyperandrogenism in PCOS patients ( 21 ). Although the aforementioned researches were done on the different region (promoter) and SNPs of CYP19 gene their results are in agreement with our results based on the fact that CYP19 gene might be correlated with PCOS predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of 11 repeat alleles are also commonly found in Chinese women with PCOS [ 97 , 98 ] which influence lipid metabolism [ 97 ]. Another polymorphism, rs2470152, did not affect PCOS risk but the heterozygous TC genotype was found to be significantly associated with increased testosterone levels with decreased E2/T ratio, suggesting role of this polymorphism in regulating aromatase activity [ 99 ]. A missense polymorphism, Arg264Cys, increases aromatase activity and affects PCOS susceptibility [ 100 ].…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Our results showed that the CYP19A1 promoter methylation level was significantly higher in PCOS samples than in controls. The E 2 /T ratio was used as an indirect measure for aromatase activity [24]. Compared with controls, PCOS had lower levels of E 2 /T (p < 0.05), and CYP19A1 mRNA and protein levels were both significantly lower in PCOS ovaries than in control samples.…”
Section: Discussionmentioning
confidence: 99%